2022
DOI: 10.3390/jcm12010204
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Survival after Extended Sleeve Lobectomy (ESL) for Central Non-Small Cell Lung Cancer (NSCLC): A Meta-Analysis with Reconstructed Time-to-Event Data

Abstract: Objective: We conducted a thorough literature search on patients with central non-small cell lung cancer (NSCLC) undergoing either extended sleeve lobectomy (ESL) or pneumonectomy (PN). Methods: We identified all original research studies that compared the long-term survival of ESL versus PN from 1990 to 2022. The primary endpoints were the median overall survival (OS) and disease-free survival (DFS). Complications, operative mortality, and the reoperation rate were the secondary endpoints. Regarding the prima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…In the group of CSL patients, the majority of patients who experienced complications suffered from prolonged air leak, bronchial obstruction requiring bronchoscopy, atrial fibrillation and anemia with blood transfusion; these adverse events are not life-threatening and can be easily managed, although they may result in prolonged hospital stays. Regarding the technical complexity of CSL and the resulting potentially fatal complications associated with bronchial and/or vascular reconstruction, there are controversial findings in the literature [23]. Okada et al [12] were the first who reported the postoperative clinical and oncological results of n = 15 ESL patients at the end of the 1990s, showing no postoperative death, acceptable complications, no incidence of broncho-pleural fistula or anastomotic stenosis and complete resection achieved in all patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the group of CSL patients, the majority of patients who experienced complications suffered from prolonged air leak, bronchial obstruction requiring bronchoscopy, atrial fibrillation and anemia with blood transfusion; these adverse events are not life-threatening and can be easily managed, although they may result in prolonged hospital stays. Regarding the technical complexity of CSL and the resulting potentially fatal complications associated with bronchial and/or vascular reconstruction, there are controversial findings in the literature [23]. Okada et al [12] were the first who reported the postoperative clinical and oncological results of n = 15 ESL patients at the end of the 1990s, showing no postoperative death, acceptable complications, no incidence of broncho-pleural fistula or anastomotic stenosis and complete resection achieved in all patients.…”
Section: Discussionmentioning
confidence: 99%
“…Okada et al [12] were the first who reported the postoperative clinical and oncological results of n = 15 ESL patients at the end of the 1990s, showing no postoperative death, acceptable complications, no incidence of broncho-pleural fistula or anastomotic stenosis and complete resection achieved in all patients. Others [14][15][16]23] reported a low mortality rate (0-3%), acceptable overall and anastomotic complications (3-8.7%), a high rate of complete resection and long-term oncological outcomes comparable to those of the control group, which consisted of patients undergoing PN [14] or SSL [16]. Conversely, two other recent papers [16,17] reported four and two cases of completion of PN due to venous thrombosis (n = 2), arterial thrombosis (n = 1) or bronchopleural fistula (n = 3), respectively.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, the Shiny method has increasingly been used not only in oncology but also in other areas of of therapeutics, such as medical devices [ 20 ], surgery [ 21 , 22 ] and also in patients with COVID-19 [ 23 ]. However, oncology and oncohematology remain the two main areas of application, where the Shiny method represents a quite simple alternative to network meta-analysis [ 8 , 9 , 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Pure endobronchial neoplasms are a rare entity, and they can present various pathologies [2]. The evaluation of patients with suspected endobronchial lung cancer includes a diagnosis of the primary tumor, an assessment of the extent of spread to regional or distant lymph nodes, or to other structures [3], Preoperative Assessment Prior to Lung Resection [4] and the Thoracic Revised Cardiac Risk Index (ThRCRI) [5]. Lung tumors located centrally, endobronchial, most often have an indication Disclaimer/Publisher's Note: The statements, opinions, and data contained in all publications are solely those of the individual author(s) and contributor(s) and not of MDPI and/or the editor(s).…”
Section: Introductionmentioning
confidence: 99%